2017
DOI: 10.17219/pim/75653
|View full text |Cite
|
Sign up to set email alerts
|

The role of chitin and chitosan in peripheral nerve reconstruction

Abstract: Chitin is a natural polysaccharide commonly found in nature and chitosan is its partially deacetylated derivative. The properties of both biopolymers allow their wide use in medicine and various industries. This paper presents the possibilities offered by chitin and chitosan for the creation of neurotubes utilized in peripheral nerve repair procedures. In the initial part of this manuscript, experimental studies on both polysaccharides carried out by numerous authors have been presented and their results have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…Chitosan is a natural polysaccharide that has been demonstrated to be a good biomaterial with a wide range of biomedical and tissue engineering applications [ 10 , 11 ] due to its biocompatibility, biodegradability, low toxicity, and bioactivity. In recent studies its regenerative properties have been demonstrated in both standard and critical length nerve reconstruction [ 10 , 12 , 13 ]. These promising preclinical results confirmed that chitosan is a suitable biomaterial for peripheral nerve regeneration and in 2014 chitosan tubes have been accepted for clinical use (Reaxon ® Nerve Guide, Medovent GmbH, Mainz, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a natural polysaccharide that has been demonstrated to be a good biomaterial with a wide range of biomedical and tissue engineering applications [ 10 , 11 ] due to its biocompatibility, biodegradability, low toxicity, and bioactivity. In recent studies its regenerative properties have been demonstrated in both standard and critical length nerve reconstruction [ 10 , 12 , 13 ]. These promising preclinical results confirmed that chitosan is a suitable biomaterial for peripheral nerve regeneration and in 2014 chitosan tubes have been accepted for clinical use (Reaxon ® Nerve Guide, Medovent GmbH, Mainz, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the structural and physicochemical properties of this amino polysaccharide can be performed using a range of modern instrumentation [ 22 ]; and several review articles covering this biopolymer have been published recently [ 23 , 24 , 25 ]. There are no doubts that chitin (even without its derivative chitosan) is still of interest for applications as an adsorbent [ 23 , 26 ] and biomaterial for biomedical aims; for example, reconstruction of peripheral nerves or wound management [ 24 , 25 , 27 ]. It is worth noting here that thus far, only chitin of fungal and arthropod origins can be isolated on industrial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin is a biopolymer present in the shells of crustaceans and cuticle of and exoskeleton of arthropods [119]. Chitosan can be obtained from the chitin, by a process of partial deacetylation [120] commercially available by alkaline hydrolysis [121], and can be found in nature in some fungi [122].…”
Section: Chitosanmentioning
confidence: 99%
“…The combined approaches aim to speed up the regenerative process and to decrease the secondary effects related to the degradation of chitosan. The chitosan polymer and its short chains do not cause an inflammatory response [135], but the fragments of its degradation can cause inflammation, leading to apoptosis of the regenerating cells and proliferation of fibrous tissue around the NGCs [119].…”
Section: Chitosanmentioning
confidence: 99%
See 1 more Smart Citation